2007
DOI: 10.1002/art.22617
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of patients with rheumatoid arthritis: Outcome of infliximab failures switched to etanercept

Abstract: Objective. The role of alternative tumor necrosis factor (TNF) antagonist therapies in the context of failure of initial TNF antagonist therapy in patients with rheumatoid arthritis (RA) has yet to be clearly defined. The goal of this study was to determine the efficacy of etanercept in patients who failed to respond to infliximab. Methods. Ninety-five patients with RA who failed to respond to infliximab and methotrexate were treated with etanercept (with continuation of concomitant methotrexate). Thirty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
33
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 14 publications
9
33
1
6
Order By: Relevance
“…Seven uncontrolled observational studies [98][99][100][101][102][103][104] were identified that assessed efficacy of ETN.…”
Section: Etanerceptmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven uncontrolled observational studies [98][99][100][101][102][103][104] were identified that assessed efficacy of ETN.…”
Section: Etanerceptmentioning
confidence: 99%
“…In studies by Haraoui et al, 98 Cohen et al 100 and Buch et al 101 patients discontinued IFX owing to a lack of efficacy or safety. In Iannone et al, 102 patients had to have 94 only reported 'EULAR response' without providing further detail.…”
Section: Etanerceptmentioning
confidence: 99%
See 3 more Smart Citations